Efeito da interferência com a neurotransmissão do óxido nítrico na proteção pulpar indireta - Cupertino, Rogério Rodrigues (2010)
Comprehension of molecular mechanisms involved in the control of blood flow and dental pulp inflammation as well as the introduction of new materials to be used in the dental pulp conservative procedures are important for the dentistry clinic. The aim of the present work was to evaluate the dental pulp state after indirect pulp capping using substances that interfere with nitric oxide (NO) neurotransmission such as L-NAME and Sildenafil, incorporated to a polymeric bioadhesive system (gel). Male Wistar rats were submitted to maxillary and jaw first molars class I cavity preparation (experiment I) followed by indirect pulp capping (experiment II), and the pulp state was evaluated considering the inflammatory infiltrate. The most intense inflammatory response was observed three days after cavity preparation. Seemingly, the use of the gel of polymeric intensified the inflammatory response. Dual effect was observed with gel plus Sildenafil. While in low concentration Sildenafil (0.015% w/w) promoted a positive effect on the pulp state, in larger concentration (Sildenafil 0.15% w/w) it caused severe inflammatory response and pulp necrosis. This is a pioneer study using a polymeric bioadhesive and thermosensitive system (gel) containing substances that interfering with NO neurotransmission in the indirect pulp protection. The present results show that the NO concentration may be determinant in the pulp response, since Sildenafil 0.015% promotes decrease of the inflammatory process and improve the pulp state, while Sildenafil 0.15% induces inflammation and necrosis. Future studies on verification of the effects of the polymeric gel in the dental pulp response, as well as of the probable molecular mechanisms related to the effects of Sildenafil in the protection indirect pulp should be conducted.